Front Matter - Teixeira, Leopoldo; Vergilio, Silvia; Canedo, Edna Dias; Maia, Marcelo; Machado, Ivan; Barcellos, Monalessa; Souza, Cleidson R. B. de; Colanzi, Thelma E.; França, César; Kohl, Karina (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Este documento traz o front matter dos Anais do SBES 2025.